APLIKASI SEVEN TOOLS DALAM PENGENDALIAN MUTU SELADA DI CV. ABC - Hidayat, Hety Handayani; Rahmawati, Ai Deti (Journal of Agricultural and Biosystem Engineering Research, 2023)
CV ABC is a company that produces organic vegetables in Yogyakarta. Lettuce plants at CV ABC are one of the plants that are in great demand by consumers and have a fairly high level of sales. The purpose of this study is to identify the quality control of lettuce with the seventools method. The tools used include check sheets, histograms, pareto charts, control charts, and cause-and-effect diagrams (fishbone). In the research that has been done, it has been shown that there are two types of damage, namely leaf spots of 725 g and torn leaves of 1385 g. Total damage as a whole is 2110 g with an average percentage of damage reaching 21.1% of the total sample of 10000 g. Causes of product defects identified from various aspects, including humans, machines, methods, materials and the environment.